Puppet Master, Puppet and Set Designer in Family Business Successions - Vaz, Samir Lotfi; Perdigão, Denis Alves; Carrieri, Alexandre de Pádua (Revista Interdisciplinar de Gestão Social, 2020)
This article seeks to analyze the process of succession in a Brazilian family business. Empirically, a qualitative research was carried out in this large company. We analyzed the empirical corpus using the Bourdieusian perspective and a Linguistic Analysis of Discourse. Our data show that the succession of executives in organizations is much more than a simple exchange of agents. Succession, as a game of power relations, involves planning, cunning, knowledge of the field, a certain domain of illusio, doxa and nomos, and use of capital. This power play can involve manipulations and bluffs. In a way, we have observed that the use of the Bourdieusian categories helped us to better understand this game in the field of administration of large family businesses.